Psychometric Properties of the Chinese Version of Anxiety Sensitivity Index-3 in Women Diagnosed With Breast Cancer - Han, Yan; Zhu, Jiang; Li, Lingyan; Zhou, Huan; Li, Shichen; Zhang, Jinqiang; Fan, Jie; Yang, Yanjie; Luo, Xingwei; Zhu, Xiongzhao (Frontiers in Psychology, 2020)
Background: Anxiety sensitivity (AS) is a trait-like predisposing factor for the prevalence of anxiety in patients diagnosed with breast cancer. The Anxiety Sensitivity Index-3 (ASI-3) has been widely used in both general and clinical samples for measuring AS. However, the data about its psychometric properties in women with breast cancer are deficient. In addition, there is no evidence proved the measure equivalence of ASI-3 across sociodemographic variables in the specific sample. Thus, the present study examined the psychometric properties and conducted measure equivalence testing of ASI-3 in Chinese women diagnosed with breast cancer. Method: This study included 815 Chinese women diagnosed with breast cancer. Single group confirmatory factor analysis (CFA) was administrated to detect the factorial validity of ASI-3 and multigroup CFAs were conducted to test the measurement equivalence of ASI-3 across various sociodemographic variables. The reliability of ASI-3 were tested by Cronbach’s alpha coefficient, Guttman split-half coefficient, McDonald's omega coefficient and test-retest coefficient. The standardized factor loadings, construct reliability (CR) and the average variance extracted (AVE) of factors were used to measure the construct validity of ASI-3 and the partial correlations were conducted to examine the criterion-related validity of ASI-3. Results: The ASI-3 had satisfactory reliability and validity in Chinese women diagnosed with breast cancer; three-factor model fitted the data well in CFA and reached partial strict invariances across age, education and residence groups. Conclusion: This study explored the psychometric properties and measurement invariance across sociodemographic variables of ASI-3 in Chinese women diagnosed with breast cancer. Our results not only proved that the ASI-3 is an appropriate instrument for measuring AS but also deepened the understanding of ASI-3 in Chinese women with malignancy.